Solvatochromic Study of Highly Fluorescent Alkylated Isocyanonaphthalenes, Their π‐Stacking, Hydrogen‐Bonding Complexation, and Quenching with Pyridine. Issue 16 (28th August 2014) - Nagy, Miklós; Rácz, Dávid; Lázár, László; Purgel, Mihály; Ditrói, Tamás; Zsuga, Miklós; Kéki, Sándor
Abstract Mono‐ and dialkylated derivatives of 1‐amino‐5‐isocyanonaphthalene (ICAN) were studied as new members of a multifunctional, easy‐to‐prepare fluorophore family, which showed excellent solvatochromic properties. The monoallyl derivative and the starting ICAN exhibited strong fluorescence quenching in the presence of small amounts of pyridine. The formation of a hydrogen‐bonded ground‐state pyridine complex was detected; however, analysis of quantum chemical calculations suggested the presence of an additional π‐stacked pyridine complex. The Stern–Volmer plot of the quenching process exhibited a downward curvature and after reaching a minimum the fluorescence intensity increased back to a significant level at high pyridine concentrations. Significant fluorescence was observed even in pure pyridine. A new mechanism and a simple mathematical equation were derived to explain the downward curvature and the remaining fluorescence by the formation of a fluorescent π‐stacked complex.